Classification of STR allelic variation using massively parallel sequencing and assessment of flanking region power. (September 2020) - Devesse, Laurence; Davenport, Lucinda; Borsuk, Lisa; Gettings, Katherine; Mason-Buck, Gabriella; Vallone, Peter M.; Syndercombe Court, Denise; Ballard, David
Highlights: Extensive allelic variation found within and outside of autosomal STR repeat regions. Sequence-based allelic frequencies must be available for massively parallel sequencing implementation. Over 1000 samples from 5 population groups were genotyped using the MiSeq FGx™ Forensic Genomics System. The gain in polymorphism achieved when analysing flanking regions is less than might be expected. Abstract: The application of massively parallel sequencing (MPS) to forensic genetics has led to improvements in multiple aspects of DNA analysis, however, additional complexities are concurrently associated with these advances. In relation to short tandem repeat (STR) typing, the move to sequence rather than length-based methodologies has highlighted the extent to which previous allelic variation was masked – both within and outside of the repeat regions (the flanking regions). In order to fully implement MPS for autosomal STR analysis, sequence-based allelic frequencies must be available, and concordance with previous typing techniques needs to be assessed. In this work, a series of samples (n = 1007) from five different population groups were genotyped using the MiSeq FGx™ Forensic Genomics System. Results were compared to those obtained using capillary electrophoresis (CE), and sequence variation has been characterised both within and outside STR repeat regions, with allelic frequencies provided for all variants observed within this database. Analysing and characterising flanking region sequence is currently less straightforward than studying repeat region variation alone, and the added value of doing so remains largely unexplored – this paper provides data to show that the gain in polymorphism achieved when analysing flanking regions is less than might be expected. In the White British population for example, including the sequence variation within repeat regions of 26 autosomal STRs made the average combined random match probability (RMP) over 700 times lower than with length-based alleles alone. Including the sequence variation within the flanking regions only resulted in a combined RMP that was a further 4 times lower.